Genetic Determination of Enzymes Synthesizing O-Specific Sugars of Salmonella Lipopolysaccharides - Nikaido, Hiroshi (1966)
Nikaido, Hiroshi (Massachusetts General Hospital, Boston, Mass.), Kishiko Nikaido, and P. Helena Mäkelä. Genetic determination of enzymes synthesizing O-specific sugars of Salmonella lipopolysaccharides. J. Bacteriol. 91:1126–1135. 1966.—Levels of enzymes involved in the biosynthesis of various nucleotide sugars were examined in parental strains and recombinants obtained in crosses between Salmonella of groups B, C(2), and C(1) with the O antigen specificities 4, 5, 12; 6, 8; and 6,7, respectively. The results showed that smooth strains of groups B and C(2) possessed the enzymes for the synthesis of guanosine diphosphate mannose, cytidine diphosphate abequose, and thymidine diphosphate rhamnose; these sugars are constituents of their lipopolysaccharides. Group C(1) lipopolysaccharide is devoid of both abequose and rhamnose, and the corresponding enzymes for cytidine diphosphate abequose synthesis, as well as the enzyme(s) catalyzing the last step(s) of thymidine diphosphate rhamnose synthesis, were undetectable in S. montevideo of this group. Two other enzymes also involved in the biosynthesis of thymidine diphosphate rhamnose were present at a low level of activity; their function in this strain is not known. The analysis of enzyme levels in recombinants indicated that genes determining at least eight of the enzymes involved in the biosynthesis of nucleotide-bound mannose, rhamnose, and abequose were located in the O locus known to determine the specificity of the O antigen. In three rough recombinant strains, enzyme levels indicated that crossing-over had presumably occurred within the O locus. The results also suggested a high degree of nonhomology in this region of the chromosome between groups B and C(1).